Regulating Production Sharing Contract in Act on Oil and Gas - Topan Meiza Romadhon (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The concept of production sharing contract in Indonesia  has experienced various changes or amendments. However, the implementation of such concept in acts pertinent to petrol and natural gases remain unclear. The detailed regulation on this aspect do not deliver sufficient elucidation, including in some significant clauses.  It is considered therefore that in the near future, the legal framework pertaining to this matter shall encompass clear and detailed provisions.Keywords: Production Sharing Contract, Act on Petroleum and Natural Gases.